Controllable biosynthesis and characterization of α-ZnS and β-ZnS quantum dots: Comparing their optical properties. (December 2016) - Yue, Lei; Qi, Shiyue; Wang, Jia; Cai, Jinhui; Xin, Baoping
Abstract: The controllable biosynthesis of α-ZnS and β-ZnS quantum dots by Clostridiaceae sp. using different concentration of hydroxypropyl starch as dispersant are demonstrated. The structure and properties are characterized by XRD, TEM, HRTEM, UV–Vis and fluorescence spectra, and so on. The results indicate that the α-ZnS quantum dots with wurtzite structure and diameter of 8±2 nm were attained under low dose of hydroxypropyl starch, while high dose obtained the β-ZnS quantum dots with sphalerite structure and diameter of 4±1 nm. The UV–Vis absorption of β-ZnS quantum dots have an evident red shift compared with α-ZnS quantum dots, and the as-biosynthesized β-ZnS quantum dots have a stronger fluorescence activity than α-ZnS quantum dots. This work displays a simple biosynthetic method to control the crystal structure and particle size of metal sulfide nanoparticles under mild conditions.